AB0815 Intraarticular Triamcinolone plus Mepivacaine Provides A Rapid and Sustained Relief for Acute Gouty Arthritis. (15th July 2016) - Andrés, M.; Begazo, A.; Sivera, F.; Vela, P.; Pascual, E.
Abstract : Background: Gout attacks are often considered as especially painful. Effective treatments for gout attacks - colchicine, NSAIDs, systemic or intra-articular corticosteroids, IL-1 blockers -result in a rapid subsidence of the attacks, but it usually requires 1–3 days (1–3) to relieve the symptoms. Our standard procedure in clinics is to add 2% mepivacaine to intra-articular triamcinolone, as we have repeatedly observed a very rapid and persistent subsidence of pain. Here we aimed to document this outcome in a prospective way. Methods: Consecutive patients with crystal-proven gout and an acute, monoarticular attack were recruited. All cases were treated with an intra-articular injection of triamcinolone plus 2% mepivacaine, according to our clinical practice. Joint pain was registered using a 0–4 Likert semiquantitative scale (0=absent; 4=severe) at baseline and 15min, 6h, 24h, and 72h after the injection. Presence of joint swelling and erythema was also collected at baseline and after 72h. Treatment response after 72h was evaluated by both the physician and the patient on a 0–4 Likert scale (0=no effect; 4=complete resolution). Between-after comparisons were analyzed using Wilcoxon signed-rank test. Results: A total of 24 patients were recruited, median (±SD) aged 64.8 years (±12.7), 22 males. Involved joints were 16 first metatarsophalangeal (1MTP), 5 knees, 2 wrists, and one ankle. Triamcinolone doses ranged from 10mg (1MTP) to 20–40mg (others). Median (p25–75) pain at baseline was 3 (2–3.8), joint swelling was present in all cases, and in 13 cases (54.2%) erythema was observed. After the intra-articular injection, a significant pain reduction was observed at all time-points, even at 15min after the injection, as shown in the Figure . No symptoms rebounds between time-points were reported. Treatment was effective as assessed by both patients and rheumatologists (3 (3–4) and 3.5 (3–4), respectively). Conclusions: This small study confirms a rapid relief of gout attacks with adding mepivacaine to intra-articular corticosteroids, with a significant response even at 15min after the injection. Large, controlled studies should confirm these results. References: Cochrane Database Syst Rev. 2014;9:CD010120. Arthritis Rheum. 2010;62:1060. Ann Rheum Dis. 2012;71:1839. Disclosure of Interest: M. Andrés Speakers bureau: Menarini, A. Begazo: None declared, F. Sivera: None declared, P. Vela: None declared, E. Pascual: None declared